Penerapan Strategi Kepemimpinan Transformasional dalam Meningkatkan Kinerja Organisasi Pendidikan - Lamirin; Joko Santoso; Panir Selwen (Jurnal Ilmiah Kanderang Tingang, 2023)
In this ever-evolving and complex context, the need for leaders who are able to face various challenges in the world of education is increasingly important. Transformational leadership, which focuses on motivating and inspiring organizational members to reach their full potential, has been recognized as a potentially powerful approach to coping with change and achieving better results. Through this research, it adopts a library research approach with the aim of gathering information and scientific papers related to literature reviews in the field of literature. The results of the analysis show that the implementation of transformational leadership strategies has a significant impact on the performance of educational organizations. Leaders who adopt this approach are able to create an inspiring work environment, encourage innovation, and develop collaboration among staff and faculty members. The ability to articulate a strong vision, provide intrinsic drive, and facilitate ongoing professional development are key elements of successful transformational leadership. However, several challenges were found in the implementation of transformational leadership strategies, such as resistance to change and the need for adequate support and training. Therefore, this research also suggests steps that can be taken to overcome these obstacles and maximize the benefits of implementing transformational leadership strategies in improving the performance of educational organizations. In conclusion, the implementation of transformational leadership strategies has a significant role in improving the performance of educational organizations. By inspiring, motivating and developing individuals, leaders who adopt this approach are able to create a productive and innovative work environment. As such, this research contributes to our understanding of how transformational leadership can be an important factor in achieving success in educational organizations.